2004
DOI: 10.2903/j.efsa.2004.16
|View full text |Cite
|
Sign up to set email alerts
|

Opinion of the Scientific Panel on additives and products or substances used in animal feed (FEEDAP) on the efficacy and safety of the coccidiostat Koffogran

Abstract: SUMMARYKoffogran is a feed additive intended for control of coccidiosis, a debilitating protozoal infection in poultry. In common with a number of other coccidiostats, Koffogran is due for evaluation to comply with statutory requirements agreed at an EU-level. The European Commission asked the EFSA to evaluate the product and advise the Commission on its efficacy and safety. Within EFSA this task was allocated to the Scientific Panel on Additives and Products or Substances used in Animal Feed (FEEDAP Panel). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Rinkinen [ 128 ] demonstrated that some Enterococcus faecium strains promoted the adherence of the zoonotic pathogen Campylobacter jejuni in the intestines of canines. Notably, the administration of E. faecium strain SF68 (deposited as strain NCIMB 10415), which originated from infant feces in 1968, reduced the occurrence of diarrhea in dogs and cats housed in animal shelters [ 45 ], and it has been verified that the strain may not cause any safety concerns for companion animals and their owners [ 129 - 131 ]. Due to these conflicting outcomes, stringent safety evaluations are required in a strain-specific manner with regard to probiotic use.…”
Section: Safety Issues Of Probiotics and The Gut Microbiome In Compan...mentioning
confidence: 99%
“…Rinkinen [ 128 ] demonstrated that some Enterococcus faecium strains promoted the adherence of the zoonotic pathogen Campylobacter jejuni in the intestines of canines. Notably, the administration of E. faecium strain SF68 (deposited as strain NCIMB 10415), which originated from infant feces in 1968, reduced the occurrence of diarrhea in dogs and cats housed in animal shelters [ 45 ], and it has been verified that the strain may not cause any safety concerns for companion animals and their owners [ 129 - 131 ]. Due to these conflicting outcomes, stringent safety evaluations are required in a strain-specific manner with regard to probiotic use.…”
Section: Safety Issues Of Probiotics and The Gut Microbiome In Compan...mentioning
confidence: 99%